Live Feed Combination for knife fish -Chitala lopis) - Mas Tri Djoko Sunarno; Mas Bayu Syamsunarno (JURNAL PERIKANAN DAN KELAUTAN, 2015)
This study in aiming to evaluate response of knife fish to various life fish species as a diet sources in controllable tank. After adapting to experimental condition, 36 tested fish collected from nature of 326.6 ± 184.1 g in individual weight were randomly stocked in 7 fiber tanks at a rate of 4-5 fish per tank and fed on life fishes in fingerling size at different combinations (common carp, tilapia, shrimp, carp+tilipia, tilapia+shrimp, carp+tilapia+shrimp) every 6 hours for 5 days of culture period. The result showed than knife fish prefer combination life food of common carp and tilapia, and then followed by common carp, tilapia and shrimp. Night was feeding time for knife fish.